Ivermectin excretion by isolated functionally intact brain endothelial capillaries - Nobmann, Stephanie; Bauer, Björn; Fricker, Gert (British journal of pharmacology, 2001)
Functionally intact brain endothelial capillaries were isolated from porcine brain. p-Glycoprotein was localized at the lumenal membrane of intact capillaries by immunohistochemistry using a murine monoclonal antibody and a secondary FITC fluorescent labelled anti-mouse IgG. Western blot staining of p-glycoprotein in isolated endothelial cells confirmed the immunohistochemistry. Excretion of the fluorescent labelled anthelmintic drug Ivermectin (BODIPY-Ivermectin) was studied in the isolated brain endothelial capillaries. Drug accumulation in the capillary lumen was visualized by fluorescence confocal laser scanning microscopy and was measured by image analysis. Secretion of BODIPY-Ivermectin into the capillary lumen exhibited characteristics of specific and energy-dependent transport. Steady state lumenal fluorescence intensity averaged 1.6 times cellular fluorescence and was reduced 3 - 4 times below cellular levels when metabolism was inhibited by NaCN. BODIPY-Ivermectin secretion was inhibited in a concentration-dependent manner by unlabeled Ivermectin. In addition, lumenal but not cellular fluorescence intensity was significantly decreased when capillaries were incubated with PSC-833, Cyclosporin A or Verapamil, all inhibitors of p-glycoprotein. Conversely, unlabelled Ivermectin reduced the p-glycoprotein (Pgp)-mediated secretion of a fluorescent derivative of Verapamil, (BODIPY-Verapamil). BODIPY-Ivermectin secretion was not affected in the presence of Leucotriene C4 (LTC4), a potent inhibitor of multidrug resistance related protein (mrp)-mediated transport processes. In addition, excretion of Fluorescein-Methotrexate, an mrp-substrate, was not inhibited by Ivermectin. Uptake experiments with isolated porcine brain capillary cells showing increased cellular uptake of BODIPY-Ivermectin in the presence of unlabelled drug or PSC-833 supported the findings of a Pgp interaction in intact capillaries. The data are consistent with BODIPY-Ivermectin and Ivermectin being transported across the lumenal membrane of brain capillaries. For the first time Pgp-interaction of Ivermectin at the blood brain barrier is demonstrated on a cellular level in an intact vascular tissue.